Design principle-based stimuli for improving creativity during ideation. (January 2019) - Perez, Blake; Hilburn, Skyler; Jensen, Dan; Wood, Kristin L
The conceptualization of new designs involves several phenomena. Research indicates that new ideas are rarely, if ever, wholly novel ideas. Instead, new ideas are formed from combinations of existing ideas, supported by synthesis, transformation, analogy, morphing, and replacement. Moreover, while much research has explored the negative implications of fixation from examples and stimuli, there exists an emerging need to study potentially positive effects of inspirational cases. Many works have studied designers' exploratory practices of solution spaces revealing active discovery and investigation of similar solutions as analogies. These exploratory practices enable designers to better understand a problem and inspire new solutions. In this work, the authors demonstrate directed use of design principles as design inspiration to improve outputs of the ideation process. Specifically, this work focuses on design principles for the particular domain of additive manufacturing, but the results suggest avenues to generalize the process with design principles from different areas. In this study, the authors created a set of physical cards to communicate a derived set of design principles. Each card is comprised of three main elements: (i) a textual description of the principle, (ii) a simplified visual representation of the principle, and (iii) an example of a real world application of the principle. Participants (N = 61) were allotted two equally timed rounds to ideate solutions for a standard design problem and given a set of the design principle cards as an intervention between the first and second rounds. Idea quantity, quality, and novelty were measured per round. Results showed no significant change in quantity—an improvement over the established trend of a decline over consecutive sessions without stimulus. Significant improvements in quality and novelty, however, were measured, indicating that the cards did assist designers in ideation. The results demonstrate that the principles, formatted as discussed, provide real avenues to arrive at innovative solutions.